Osteological Investigations of the Animal Remains Recovered from the Excavations of Ancient Sardis / Tarihsel Sard şehri hayvan kalmtıarı üzerinde osteolojik etüdler - Doğuer, Sabri (1966)
Anadolu = Anatolia; 1964; also bones from the Lydian Period (about 1000-547 B.C.), Late Bronze Age and Early Iron Age (about 1400-1000 B.C.).